Die besondere Kontur von Bonhoeffers Mystik. Thomas von Kempen als spiritueller Impulsgeber Dietrich Bonhoeffers - Zimmerling, Peter (Evangelische Theologie, 2017)
This essay aims at corroborating the thesis that Dietrich Bonhoeffer’s spirituality contains a mystical dimension owing its characteristics to Thomas à Kempis’ Imitatio Christi. First the role of the Imitation of Christ in Bonhoeffer’s life and work is explained. A second part shows concrete substantial parallels between Bonhoeffer and Thomas à Kempis, primarily based on citations from Bonhoeffer’s oeuvre. Finally the essay tries to sketch the specific mystical profile of Bonhoeffer’s spirituality. A short review of the history of research precedes each part.